2016
DOI: 10.1093/intqhc/mzw114
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with ambulatory care in Germany: effects of patient- and medical practice-related factors

Abstract: All factors studied, specifically the patients' self-rated health, affected patient satisfaction. Adjustment should always be considered because it improves the comparability of patient satisfaction in medical practices with atypically varying patient populations and increases the acceptance of comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Up to now, there is a lack of scientific information on the patient satisfaction with outpatient care after pediatric and adult heart transplantation and the correlation with other factors in these special patients. An analysis of the ZAP survey of over 9000 patients revealed a mild correlation between gender and age and the satisfaction with the outpatient care [20]. The strongest positive effect on the patient satisfaction with the outpatient care could be seen in terms of the self‐rated health [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there is a lack of scientific information on the patient satisfaction with outpatient care after pediatric and adult heart transplantation and the correlation with other factors in these special patients. An analysis of the ZAP survey of over 9000 patients revealed a mild correlation between gender and age and the satisfaction with the outpatient care [20]. The strongest positive effect on the patient satisfaction with the outpatient care could be seen in terms of the self‐rated health [20].…”
Section: Discussionmentioning
confidence: 99%
“…It evaluates the patient satisfaction with outpatient care on four dimensions (patient–physician interaction, information, office organization, and professional competence). The survey was evaluated with two samples with over 2300 patients from outpatient clinics and showed good construct validity and high internal consistency [17,20]. Each dimension is evaluated using three to eight questions.…”
Section: Methodsmentioning
confidence: 99%
“…Moscovice and Casey (2011) as well as Tranberg et al (2018) confirmed this phenomenon in their health care studies and concluded that rural settings lead to higher patient satisfaction. Furthermore, subjective health status is associated with life satisfaction and patient satisfaction respectively (Auras et al , 2016; Ngamaba et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One problem is that studies in this field often used different type and sources of data and those are very heterogeneous. Even in Central Europe, and Germany more precisely, performed studies used different sources (Schoenfelder et al , 2011; Emmert et al , 2015; Auras et al , 2016; Schaal et al , 2016; Kraska et al , 2017; Zich and Tisch, 2018). Internationally the same problems were found (Batbaatar et al , 2017; Woodward et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Самооцінка здоров'я пацієнтами мала найсильніший ефект (максимальний коефіцієнт регресії 7,66, ДІ 6,69) за рейтингом задоволеності. [15] Дослідження, яке було проведене в Уганді серед відвідувачів семи амбулаторних поліклінік мало на меті визначити фактори, які пов'язані із загальною задоволеність амбулаторною допомогою. Це було кроссекційне дослідження, в якому пацієнти були опитані на виході з амбулаторії.…”
unclassified